(untitled) (CIPEEX, 2022)
THIS INTEGRATIVE LITERATURE REVIEW AIMS TO EVALUATE THE IMPACTS OF PLATELET-RICH PLASMA (PRP) TREATMENT IN THE TREATMENT OF KNEE OSTEOARTHRITIS IN THE ELDERLY, SINCE IT HAS BEEN GAINING MORE AND MORE SPACE IN THE MEDICAL FIELD SINCE ITS DEVELOPMENT. THE MAIN PURPOSE OF THIS STUDY IS TO ELUCIDATE THE IMPACTS OF PLATELET RICH PLASMA (PRP) TREATMENT IN THE TREATMENT OF KNEE OSTEOARTHRITIS IN THE ELDERLY.&NBSP; THIS PAPER HAS BEEN DIVIDED INTO FIVE PARTS. IN THE INTRODUCTION THERE IS A BRIEF CLARIFICATION OF TWO KEY CONCEPTS OF THE RESEARCH - OSTEOARTHRITIS (OA) AND PLATELET RICH PLASMA. IN THE METHODOLOGY, ALL THE SEARCH CRITERIA AND STRATEGIES USED TO OBTAIN THE ARTICLES USED IN THE RESEARCH ARE COVERED: PICO STRATEGY, DETERMINATION OF A GUIDING QUESTION AND INCLUSION AND EXCLUSION CRITERIA. IN THE RESULTS, FROM 5 TABLES, DIVIDED ACCORDING TO THE CATEGORIES DETERMINED FOR GROUPING THE ARTICLES FOUND, A PRESENTATION OF THE MAIN DATA ADDRESSED IN EACH DOCUMENT WAS MADE. IN THE DISCUSSION, AN ANALYSIS OF THE DATA FOUND IS PRESENTED, AND IT WAS NOTED THAT PRP CONSTITUTES A CONSIDERABLE MEANS OF TREATMENT FOR THE SYMPTOMS OF KNEE OSTEOARTHRITIS IN THE ELDERLY WHEN COMPARED TO OTHER METHODS, BUT IT STILL PRESENTS DIFFICULTIES FOR ITS EFFICIENT ESTABLISHMENT IN THE MEDICAL FIELD, SUCH AS THE LACK OF STANDARDIZATION IN THE COMPOSITION, AMOUNT, AND NUMBER OF DOSES TO BE APPLIED TO EACH PATIENT. THEREFORE, IN CONCLUSION, IT WAS EVIDENT THAT THE PROPOSED OBJECTIVE WAS COMPLETED.